(untitled) (Pedagogy of Higher and Secondary Education, 2014)
In the article the didactic aspect of the problem of providing emotion of teaching students is beign studied. Pedagogical sense of the notion "teaching emotion" has been theoretically substantiated and experimentally tesyed.